The role of ginger (Zingiber officinale) in the management of nausea and vomiting - Choroszewska, Ewelina; Wojciechowska, Karolina; Zabrocka, Patrycja; Martowska, Julia; Baran, Julia; Bullmann, Agnieszka; Warych, Wiktor; Niezgoda, Julia; Skłodowski, Tomasz; Woroniecka, Katarzyna (Quality in Sport, 2026)
Nausea and vomiting are common and clinically relevant symptoms associated with a wide range of medical conditions, including chemotherapy and radiotherapy, surgical procedures, pregnancy, and gastrointestinal disorders. Their pathophysiology involves complex interactions between central and peripheral nervous system pathways, neurotransmitters, inflammatory mediators, and gastrointestinal motility. Ginger (Zingiber officinale), a medicinal plant traditionally used to alleviate gastrointestinal discomfort, contains bioactive compounds such as gingerols and shogaols that exhibit anti-inflammatory, prokinetic, and neuro-modulatory properties. This article provides a narrative review of current clinical and experimental evidence regarding the role of ginger in the management of nausea and vomiting, with particular emphasis on chemotherapy-induced nausea and vomiting, postoperative nausea, nausea of pregnancy, and selected gastrointestinal conditions.